Microbial Ecology of Methanotrophy in Streams Along a Gradient of CH4 Availability - Bagnoud, Alexandre; Pramateftaki, Paraskevi; Bogard, Matthew J.; Battin, Tom J.; Peter, Hannes (Frontiers in Microbiology, 2020)
Despite the recognition of streams and rivers as sources of methane (CH4) to the atmosphere, the role of CH4 oxidation (MOX) in these ecosystems remains poorly understood to date. Here, we measured the kinetics of MOX in stream sediments of 14 sites to resolve the ecophysiology of methane oxidizing bacteria (MOB) communities. The streams cover a gradient of landcover and associated physico-chemical parameter and differed in stream- and porewater CH4 concentrations. Michealis-Menten kinetic parameter of MOX, Vmax (maximum rate) and KS (CH4 concentration at half Vmax) increased with CH4 supply. KS values in the micromolar range matched the CH4 concentrations measured in shallow stream sediments and indicate that MOX is mostly driven by low-affinity MOB. 16S rRNA gene sequencing identified MOB classified as Methylococcaceae and particularly Crenothrix. Their relative abundance correlated with pmoA gene counts and MOX rates, underscoring their pivotal role as CH4 oxidizers in stream sediments. Building on the concept of enterotypes, we identify two distinct groups of co-occurring MOB. While there was no taxonomic difference among the members of each cluster, one cluster contained abundant and common MOB, whereas the other cluster contained rare OTUs specific to a subset of streams. These integrated analyses of changes in MOB community structure, gene abundance and the corresponding ecosystem process contribute to a better understanding of the distal controls on methane oxidation in streams.